2023
DOI: 10.3390/ijms24108979
|View full text |Cite
|
Sign up to set email alerts
|

The Essential Role of Light-Induced Autophagy in the Inner Choroid/Outer Retinal Neurovascular Unit in Baseline Conditions and Degeneration

Abstract: The present article discusses the role of light in altering autophagy, both within the outer retina (retinal pigment epithelium, RPE, and the outer segment of photoreceptors) and the inner choroid (Bruch’s membrane, BM, endothelial cells and the pericytes of choriocapillaris, CC). Here autophagy is needed to maintain the high metabolic requirements and to provide the specific physiological activity sub-serving the process of vision. Activation or inhibition of autophagy within RPE strongly depends on light exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 126 publications
(242 reference statements)
1
0
0
Order By: Relevance
“…Interestingly, light seems to regulate autophagy in clock neurons, since in constant darkness the pattern of daily changes in early and late autophagosomes was different that in LD12:12 and autophagy flux was higher. However, we observed very low level of early autophagosomes in the lLNv terminals in the medulla of flies kept in constant darkness, which correlates with the data which showed that autophagy is light-driven in the retina 56 and may be enhanced by light in hippocampal cells in vitro 57 . This phenomenon needs more exploration in the future.…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, light seems to regulate autophagy in clock neurons, since in constant darkness the pattern of daily changes in early and late autophagosomes was different that in LD12:12 and autophagy flux was higher. However, we observed very low level of early autophagosomes in the lLNv terminals in the medulla of flies kept in constant darkness, which correlates with the data which showed that autophagy is light-driven in the retina 56 and may be enhanced by light in hippocampal cells in vitro 57 . This phenomenon needs more exploration in the future.…”
Section: Discussionsupporting
confidence: 90%